2020
DOI: 10.5194/egusphere-egu2020-2147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global analysis of climate-relevant aerosol properties retrieved from the network of GAW near-surface observatories

Abstract: <p>Aerosol particles are essential constituents of the Earth’s atmosphere, impacting the earth radiation balance directly by scattering and absorbing solar radiation, and indirectly by acting as cloud condensation nuclei. In contrast to most greenhouse gases, aerosol particles have short atmospheric residence time resulting in a highly heterogeneous distribution in space and time. There is a clear need to document this variability at regional scale through observations involving, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…According to the available research data [23,10,32] of aerosol particles of the nanometer range in the atmosphere of the Baikal region, it was found that in the spring period the average total number concentration of aerosol in the range of 10-500 nm varies from 950 cm −3 to 10000 cm −3 . We compared the aerosol particle number concentration at the Boyarsky station with provides data for polar stations, high-altitude stations, coastal stations, remote stations and rural stations [33][34][35][36]17,37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the available research data [23,10,32] of aerosol particles of the nanometer range in the atmosphere of the Baikal region, it was found that in the spring period the average total number concentration of aerosol in the range of 10-500 nm varies from 950 cm −3 to 10000 cm −3 . We compared the aerosol particle number concentration at the Boyarsky station with provides data for polar stations, high-altitude stations, coastal stations, remote stations and rural stations [33][34][35][36]17,37,38].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Collaud Coen et al (2020) presented the most complete and up-to-date analysis of long-term trend analysis of in situ aerosol measurements derived from stations with large spatial representation from 52 observatories worldwide [18]. describe the global network, which including 16 stations in Europe, 21 in North America, 5 in Asia, 2 in Africa, 6 in the polar regions and 2 in the southwestern Pacific [19]. These stations are mostly situated in rural or remote areas [18].…”
Section: Introductionmentioning
confidence: 99%
“…Direct in situ sampling at ground stations can add physical, optical, and chemical detail to the remotely sensed particle optical properties and can document long‐term variability. However, such measurements are acquired only near or at the surface and at only a few sampling sites, mostly concentrated in a few regions of the globe (e.g., The US Interagency Monitoring of Protected Visual Environments network, IMPROVE, Malm & Hand, 2007; the Surface Particulate Matter Network, SPARTAN, Snider et al., 2015; the Global Atmospheric Watch (GAW) network, Andrews et al., 2019; Rose et al., 2021; Laj et al., 2020; the European Commission's Aerosol, Clouds, and Trace Gases Research Infrastructure (ACTRIS) (https://www.actris.eu/; last accessed: March 2023); plus studies of collected data by Burgos et al., 2020; Fanourgakis et al., 2019).…”
Section: The Role Of Aircraft and Ground‐based In Situ And Remote‐sen...mentioning
confidence: 99%
“…Stronger aerosol scattering ability (with larger SSA) can enhance reflected solar radiation from the Earth causing cooling effect, while aerosol absorbing (with lower SSA) leads to positive net radiation and contributes to warming effect. Among 31 sites connected to the Global Atmosphere Watch (GAW) network, the SSA mean values based on in situ measurement ranged from 0.8 to 1, with only six sites lower than 0.9 (Laj et al., 2020). SSA is the most sensitive factor to aerosol radiative forcing calculation compared with other optical parameters (Loeb & Su, 2010; Lu et al., 2022; McComiskey et al., 2008).…”
Section: Introductionmentioning
confidence: 99%